DIGITAL LITERACY OF ISLAMIC STUDENTS AS A NEW PARADIGM OF ISLAMIC EDUCATION: TRANSFORMING THE TRADITION OF ISLAMIC BOARDING SCHOOL LEARNING IN THE ERA OF GLOBALIZATION - Budiyanto Budiyanto; Ahmad Tanzeh; Agus Purwowidodo (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study examines digital literacy among santri as a new paradigm in Islamic education that transforms traditional learning practices in Islamic boarding schools (pesantren) amid the challenges of globalization. The rapid development of information and communication technology has encouraged pesantren to adapt their educational systems without abandoning their core values and traditions. Using a qualitative literature review approach, this study analyzes various scholarly works, policy documents, and contemporary research related to digital literacy, Islamic education, and pesantren transformation. The findings indicate that digital literacy not only functions as a technical skill in accessing, evaluating, and utilizing information but also serves as a strategic instrument for strengthening critical thinking, religious moderation, collaborative learning, and global engagement among santri. The integration of digital technology into pesantren learning systems has created a hybrid educational model that combines classical Islamic scholarship with modern digital competencies. Nevertheless, challenges remain, including disparities in technological infrastructure, digital ethics, teacher readiness, and the risk of misinformation. Therefore, strengthening digital literacy based on Islamic values is essential to developing competent, ethical, and globally competitive Muslim generations. This transformation signifies a paradigm shift in Islamic education toward a more adaptive, innovative, and sustainable future.